Long-Term Follow-Up on the Effects of Sigmoid- Rectal Pouch for Urinary Diversion - Sun, Bin; Yan, Jing-Min; Li, Jian-Ye; Guo, He-Qing; Hong, Quan; Yao, Zhi-Yong; Zhou, Gao-Biao; Pan, Guang-Xin; Li, Xian-Chu (Urology Journal, 2014)
Abstract Purpose: The aim of this study was to investigate the long-term clinical effects of sigmoidrectal pouch for urinary diversion. Materials and Methods: A total of 45 patients, including 40 males and 5 females, underwent sigmoid-rectal pouch procedure. The patients aged from 38 to 70 years with a mean age of 59 years. The postoperative follow-up ranged from 6 months to 19 years with an average of 6 years. Postoperative continence and voiding were analyzed, urinary reservoir pressure was measured and the complications of upper urinary tract were determined. The index of quality of life (QoL) in the International Prostate Symptom Score (IPSS) was used to evaluate the degree of satisfaction to urinate. Results: Forty patients had slight incontinence in the early postoperative stage and could control urination well 30 days postoperatively. The volume of pouch was 270-600 mL with an average of 375 mL. The basic pressure during filling period was 6-20 cmH2O with an average 15 cmH2O, the maximum filling pressure was 15-30 cmH2O with an average 26 cmH2O. The compliance of sigmoid-rectal pouch was fine with an average of 30 (range 18-40) mL/ cmH2O. There were no severe complications such as hyperchloremic acidosis or retrograde pyelonephritis. Six patients had slight hydronephrosis. The index of QoL were 0-2 in 20 patients, 3 in five patients and 4 in two patients. Conclusion: The sigmoid-rectal pouch operation was simple and acceptable by surgeons and patients. It may be an ideal urinary diversion for patients with muscle-invasive bladder cancer, especially for patients on whom urethrectomy should be done.